Evaluasi Penerapan Sarana Pengendalian Risiko di Bagian Produksi Tiang Pancang Bulat PT. TB PBB Wijaya Karya Beton Boyolali - Sekar Rini, Wahyu Dian; , Tarwaka, PGDip.Sc.,M.Erg (2017)
Based on accident database, workplace accidents can be caused by environment and unsafe behavior. Controlling devices applied always optimized on PPE (Personal Protective Equipment). Uncertainty situation and conditionfactors can lead to accidents.In a pile production, there are still potential hazards and extreme values as well as some cases of accidents occurred and hence this study conductedto know the application of HIRA and evaluate the availability and suitability of the risk controlling devices that had been done. The purpose of this study is to determine the availability and suitability of risk controllingdevices in an attempt to prevent workplace accident in the production department of PTWikaBoyolali. This study used Observational Descriptive method. The sample of this study was all employees that work on the morning shift at 1, 2, and 4lane. Analysis of respondents characteristic was done with univariate and the result was analysed with observational method using HIRADC form and evaluation of availability and conformity of controlling devices. The result indicated that the controllingdevices are available and compatible with the hierarchy of controls applied and can reduce the workplace accident, but still need some improvements in its implementation. Suitable PPE need to be added to optimize the controlling devices.